Edukasi dan Pelatihan Pemanfaatan Tanaman Obat Keluarga (TOGA) untuk Meningkatkan Kemandirian Obat Herbal Keluarga - Rini Susanti; Wizni Fadhillah; Efrida Lubis; Hadi Purwanto; Nurul Hayatun Nufus (CV. IRA PUBLISHING, 2026)
The use of Family Medicinal Plants (TOGA) is one of the strategies for strengthening local resource-based health that can support family herbal medicine independence. This community service activity aims to improve community knowledge and skills in cultivating and utilizing TOGA as an alternative for addressing minor health complaints. The program was implemented in Pondok Bungur Village, Rawang Panca Arga District, Asahan Regency. The activity methods included interactive counseling, planting demonstrations, simple processing practices, and mentoring. The results of the activity showed an increase in participants' understanding of the benefits, cultivation techniques, and safe and sustainable use of TOGA. This activity proved effective in promoting community health literacy and strengthening family independence in the use of local plant-based herbal medicine.